(untitled) (Palíndromo, 2017)
Think of artistic higher education in fine arts today is to think about the circumstances of the ecological context of student training and also about the way teachers work, taking into account the evidence resulting from both the artistic environment and current society and from the assumptions enumerated by educational policy. Thus this article intends to reflect on the perspectives of teaching-learning in the artistic higher education of fine arts, through the perception of the teachers, prospecting the future. This work focuses on a mixed methodological approach whose objectives are: understand how teachers perceive themselves as professionals; what dilemmas they live in nowadays and how they prospect the formation in the artistic higher education of fine arts. The emerging conclusions of the study highlight the need for curricular reform in higher artistic education, aiming at the innovation of training processes.